Autologous serum therapy in chronic urticaria: A promising complement to antihistamines - Panchami Debbarman; Amrita Sil; Piyush Kanti Datta; Debabrata Bandyopadhyay; Nilay Kanti Das (Wolters Kluwer Medknow Publications, 2014)
Background: Chronic urticaria (CU) is a vexing problem and patients of CU suffer from the morbidity that arise from irritable itch and weals and are also subjected to a huge antihistamine pill burden. The symptoms are more in autoreactive urticaria (AU) where auto-antibodies in blood flares-up the condition. Search for newer effective modalities which can reduce pill burden is a felt need. Aims: This study evaluates the effectiveness of autologous serum therapy (AST) in CU and also determines its usefulness in AU. Materials and Methods: Double blind, parallel group, randomized, controlled study. Fifty four patients were given AST and 57 patients were given injection normal saline (placebo), along with cetirizine in an on-demand basis in both groups. AST/Placebo was given weekly for nine weeks and followed-up for a total period of 24 weeks. AU was diagnosed by autologous serum skin test. Urticaria total severity score (TSS), Urticaria activity score (UAS), Dermatologic life quality index (DLQI) was used as primary effectiveness variables. Safety parameters assessed were the spontaneously reported adverse events and laboratory parameters. Results: TSS showed significant improvement from baseline, 7 th week and 8 th week onwards in AST group and placebo group respectively. Group comparison showed significant improvement 4 th week onwards. UAS showed similar results. DLQI showed significant improvement in AST group compared to placebo at the end of study. Both AU and non-AU patients showed comparable improvement of TSS. Conclusion: AST shows promise in treatment of urticaria regardless of the autoreactive nature.